Teknik Reframing Dalam Mereduksi Perilaku Agresif Remaja Dengan Konseling Individu (Studi Kasus Klien “D” Di Kelurahan Pahlawan Palembang) - Nopriyansah, Randi; Kusnadi, Kusnadi; Jannati, Zhila (CV. ITTC INDONESIA, 2022)
This research is motivated by aggressive behavior by teenagers in the Heroes Village. This study aims to determine the description of aggressive behavior of client